Cyber Library: Pengembangan Perpustakaan Online Berbasis Web Menggunakan Metode Prototyping (Studi Kasus Universitas Nasional) - Atikah Suhaimah; Agung Triayudi; Endah Tri Esthi Handayani (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
Libraries as a service to visitors who are looking for efficient learning methods through reading every book in the library. The services provided by the officer can help us as visitors not find it difficult when looking for an article that wants to know. Services that still use manual services are destructive in time efficiency. So it is difficult to find the book that we want because the officers will find the book data one by one, causing problems in time efficiency. Difficulty looking for collections and inaccurate data that has been found in damaged archives in the library service system. Libraries as part of the application in further library development, namely online-based libraries. The purpose of this research is pinned because of the rapid growth of technology in this digital era, which is now online in almost all sectors. The method that researchers will use is SDLC in the form of a waterfall model. And also designing information system prototypes at the National University library. As for those used to design this system, namely UML, Class Diagram, Use Case The results of the research and application of this website-based library makes it easier for librarians and library visitors.